2022
DOI: 10.3892/br.2022.1590
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with disease severity of COVID‑19 in patients with type 2 diabetes mellitus

Abstract: Diabetes mellitus causes a decline in immunological function, an increase in proinflammatory cytokines, and a prothrombotic state, thus providing risk factors for the severity of coronavirus disease 2019 (COVID-19) in patients with type 2 diabetes mellitus (T2DM). The aim of the present study was to analyze the risk factors associated with the severity of COVID-19 in patients with T2DM. A cross-sectional observational study was performed on 201 patients with T2DM from May 1 to August 31, 2020 and admitted to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
(110 reference statements)
0
3
0
Order By: Relevance
“…However, those with hypertension had a significantly lower risk, in agreement with a recent research showing a protective effect of antihypertensive drugs on mortality among COVID-19 patients [42]. In contrast, a study published in 2023 showed that hypertension was a driver for increased severity of cases among patients with T2D [43].…”
Section: Discussionsupporting
confidence: 85%
“…However, those with hypertension had a significantly lower risk, in agreement with a recent research showing a protective effect of antihypertensive drugs on mortality among COVID-19 patients [42]. In contrast, a study published in 2023 showed that hypertension was a driver for increased severity of cases among patients with T2D [43].…”
Section: Discussionsupporting
confidence: 85%
“…A major limitation of our study, on the other hand, is the absence of information on blood glucose or glycated hemoglobin levels, which may be confounding factors, given that a worse glycemic control has been associated with a more severe COVID-19 course [8,54,55]. Furthermore, no data on the prevalence of microvascular complications, a condition which has also been linked to a worse prognosis of COVID-19 [55], were available in our retrospective study, as well as no data on the ethnicity and socioeconomic status of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The risk for a severe form of COVID-19, even in those who received vaccination, is significantly reduced, but it may still not be negligible in patients with comorbidities [4]. Among the more frequent chronic diseases, Diabetes Mellitus (DM) has been associated with a 14-32% higher possibility of a severe course of disease [5] and a higher mortality for Coronavirus disease-19 (COVID-19), both in hospitalized patients [6] and in the general population [7], especially in those with a longer disease duration [8]. This finding is in line with previous observations which established DM as a risk factor for a more severe course of several infectious illnesses [9], including a higher risk for influenza-related hospitalization and death [10] and a higher risk for mortality for other diseases caused by coronaviruses, such as Severe Acute Respiratory Syndrome (SARS-CoV-1) [11], or Middle East Respiratory Syndrome Coronavirus (MERS-CoV) [12].…”
Section: Introductionmentioning
confidence: 99%
“…[ 38 ] In addition to this, increased severity of COVID‐19 infection in T2DM patients correlates with old age, hypertension, neutrophil‑lymphocyte ratio (NLR) ≥ 7.36 and HbA1c ≥ 8%. [ 39 ] The possible mechanisms by which pre‐existing metabolic conditions like T2DM predispose individuals toward COVID‐19 infection include hyperglycemia, more effective binding of SARS‐CoV‐2 and efficient entry into the host, impaired T‐cell function, reduced viral clearance, hyper‐inflammatory response, generation of cytokine storm and presence of comorbidities including CVD. [ 40 ] Chronic hyperglycemic conditions in T2DM are associated with increased ACE2 expression in the lungs and other tissues which promotes viral entry into the host cells.…”
Section: Covid and Diabetes Mellitusmentioning
confidence: 99%